A Basis for the Design of a Curriculum Incorporating Music and Drama in Children's English Language Instruction - Mónica Rodríguez-Bonces (Universidad Nacional de Colombia, 2017)
This article presents the foundations to design a curriculum that integrates music and drama as strategies for the teaching of English as a foreign language. Besides promoting interdisciplinarity, this curriculum seeks to improve the language level of those children attending continuing educational programs at any higher education institution. The interdisciplinary curriculum not only innovates the offer of English courses for children-music and drama-but also promotes meaningful learning and creates a positive attitude in children so that a high degree of interest in learning a foreign language exists. The article, besides explaining the basis for curriculum design, highlights the advantages of integrating music and drama as a medium for the teaching of a foreign language.